2020
DOI: 10.1093/gerona/glaa106
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Frailty from Adulthood into Old Age: Results from a 27-Year Longitudinal Population-Based Study in Sweden

Abstract: Background Frailty is a strong predictor of adverse outcomes. However, longitudinal drivers of frailty are not well understood. This study aimed at investigating the longitudinal trajectories of a frailty index (FI) from adulthood to late life and identifying the factors associated with the level and rate of change in FI. Methods An age-based latent growth curve analysis was performed in the Swedish Adoption/Twin Study of Agi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
7
27
0
Order By: Relevance
“…This hypothesis implies that prevention of frailty should start at middle age, when the first chronic diseases emerge. These findings add to the first studies of frailty trajectories in very large samples, which show a gradual increase of frailty severity from middle-age onwards [13,14], with a steeper increase after the age of 65 [19]. Moreover, the FI may gain importance for public health, because its electronic version is being implemented increasingly in routine care (https://www.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This hypothesis implies that prevention of frailty should start at middle age, when the first chronic diseases emerge. These findings add to the first studies of frailty trajectories in very large samples, which show a gradual increase of frailty severity from middle-age onwards [13,14], with a steeper increase after the age of 65 [19]. Moreover, the FI may gain importance for public health, because its electronic version is being implemented increasingly in routine care (https://www.…”
Section: Discussionmentioning
confidence: 52%
“…Whether the increased mortality risk in kidney disease that we found is a chance finding or could be explained by comorbidity with diabetes and/or cardiovascular diseases deserves further study. Current evidence on the FI in younger adult samples is scarce (e.g., [19,22,26,27]), and in larger samples limited to the UK Biobank study [13,14]. Data from5 00,000 middle-aged and older people who participated in the UK Biobank cohort showed that both an adapted version of the frailty phenotype [13] as well as the FI based on 49 self-report health deficits [14] are associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a substantial proportion of the variation of FI is shaped by environmental factors unique to individuals, although this component also includes measurement error. This may reflect the multidimensional nature of frailty, in which diverse risk factors, such as underweight, obesity and low education, have been linked to the elevated risk of frailty (1315).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large genome-wide association study (GWAS) revealed that the molecular genetic underpinnings of the FI are shared to some extent with key public health risk factors, such as body mass index (BMI), cardiovascular disease, smoking, as well as mental health traits (12). A vast body of literature has discerned the lifestyle and environmental determinants of frailty, highlighting the role of several physical, social, behavioral and psychological factors (1315). There is also a persisting socioeconomic gradient in frailty, with increasing socioeconomic adversity associated with higher frailty and contributing to health inequalities even in old age (16).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies included female twins only, leaving sex differences in the heritability of FI unaddressed. A vast body of literature has discerned the lifestyle and environmental determinants of frailty [ 12 14 ], and showed a persisting socioeconomic gradient in frailty, with increasing socioeconomic adversity associated with higher frailty and contributing to health inequalities even in old age [ 15 ]. Two of the most significant risk factors of frailty are unhealthy body mass index (BMI) ranges, including both underweight and obesity [ 16 18 ], and low educational attainment [ 12 , 19 21 ].…”
Section: Introductionmentioning
confidence: 99%